Gambaran Pola Makan, Tabu, Infeksi dan Status Gizi Balita Suku Anak Dalam di Propinsi Jambi : Gambaran Pola Makan, Tabu, Infeksi dan Status Gizi Balita Suku Anak Dalam di Provinsi Jambi - Siti Fatimah Pradigdo; Martha Irene Kartasurya; Mahalul Azam (Universitas Airlangga, 2022)
Background: In Sarolangun District, the prevalence of short nutritional status for toddlers in 2021 is 21.4%, and the prevalence of malnutrition is 14.3%, almost similar with Jambi Province data. Objectives: To determine eating habits, taboos, infection rates, and nutritional status of SAD (Suku Anak Dalam) toddlers who live in Jambi Province. Methods: This analytic descriptive study used a cross-sectional design and incidental sampling approach. The subject of 39 settled down SAD toddlers and 33 nomadic SAD toddlers was obtained. Data were gathered from interview to Demang, a trusted source for SAD, equipped with structured questionnaires and anthropometric measurements with digital scales and microtoise, which were then processed with WHO Anthro. Due to the lack of information on the age of nomadic SAD toddlers, nutritional status was determined using WHZ scores. Data analysis was carried out using the Independent T Test which was then displayed in the form of cross tabulations and diagrams. Results: SAD toddlers who are settled down usually eat rice as the staple food (2 to 3 times per day, along with vegetables, animal source food and fruit. The main food source of nomadic SAD Toddlers is tubers and boiled vegetables, and fish, which were caught during their hunting. Except fish, all animal dishes, including beef and chicken, are prohibited for nomadic SAD toddlers. None of the nomadic SAD toddlers had infection, whereas 7.69% of settled down SAD toddlers had. The incidence of poor nutritional status based on WHZ was higher in nomadic SAD toddlers (42.4%) compared to settled down SAD toddlers (28.2%), but not significant based on the Independent T Test results. Conclusions: Settled down SAD toddlers have diverse eating habits, some of them had infections, and are generally malnourished, while all of the nomadic SAD toddlers avoid to eat animal products other than fish.